The myrmicine ant genus allomerus mayr (hymenoptera: formicidae) (2007)
The Neotropical myrmicine ant genus Allomerus Mayr is revised. The genus isapparently monophyletic based on the antennal club confi guration. I recognize 8 species(4 described as new): Allomerus brevipilosus n. sp. (Brazil), A. decemarticulatusMayr (Brazil, French Guiana), A. dentatus n. sp. (Venezuela), A. maietae n. sp.(Brazil), A. octoarticulatus Mayr (=A. tuberculatus Forel n. syn. = A. octoarticulatusvar. demerarae W. M. Wheeler n. syn. = A. novemarticulatus Wheeler and amp; Mann n.syn. [Brazil, Bolivia, Colombia, French Guiana, Peru]), A. septemarticulatus Mayrstatus rev. (Brazil), A. undecemarticulatus n. sp. (Venezuela) and A. vogeli Kempf(Venezuela, Brazil). Better knowledge of the taxonomy of Allomerus is needed tounderstand the apparently sporadic differences in antennal fl agellomere number andspeciation processes that are probably linked to plant cavity colonization.